PENERAPAN MODEL PEMBELAJARAN COOPERATIVE BELAJAR DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Ahmad Syarifuddin (Ta'dib: Jurnal Pendidikan Islam, 2011)
Learning is a path to success. Learning is closely related to the process of changing. However, not all of the changing process is described as learning. Learning is a complicated aspect and involves many interrelated things. Any person who wants to perform learning activities should understand the principles of learning and the factors that affect learning. Learning principles include physical and spiritual maturity,  sincerity, purpose comprehension, have the readiness and presence of habituation. While the factors that affect learning, namely: internal factors, external, and learning approach.